The impact of the eye model choice on the results of dosage and anatomical location planning in proton therapy of intraocular neoplasms - I. N. Kancheli; Ya. P. Vladimirova (Российский офтальмологический журнал, 2018)
Purpose: To develop a program of dosage and anatomical planning of proton therapy on the basis of a 3-D model of the eye presenting the eye structure, risk areas, and the tumor. Results: Dose field calculations are made for the spherical, ellipsoidal and ovoidal model of the eyeball. The effects of the wrong choice of the model on these calculation for the tumor and the eye structures are shown. Conclusions: A wrong presentation of the volume geometry of the eye results in errors in determining the dose absorbed in critical structures. It is shown that individual density values for each structure should not be replaced by averaged values when calculating the radiological equivalent (water-equivalent) thickness, as the averaging in calculating dose distributions may lead to an underestimation of the dose absorbed in critical structures and to an incorrect matching of the target and the dose field // Russian Ophthalmological Journal, 2016; 3: 19-25. doi: 10.21516/2072-0076-2016-9-3-19-25.